2021
DOI: 10.1088/1757-899x/1176/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Annona Squamosa and Annona Muricata Seed Extracts as Ingredients in Bio-pesticides Spray

Abstract: Pesticides released chlorofluorocarbon (CFC) that can harm to the environment and human health. Therefore, it is a need for development of an alternative methods in pest management due to negative effects of pesticides for human health and the environment. The objective of this study was to evaluate the effectiveness of Annona Squamosa and Annona Muricata seed extracts as ingredients in bio-pesticides spray on killing crickets (Gryllidae) and mealworm (Tenebriomolitor). The seeds of Annona Squamosa and Annona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…These acetogenins are inhibitors of mitochondrial complex I and are therefore known to be neurotoxic in humans and rats. Other studies have demonstrated the effectiveness of the oil on insects of the order Diptera [17,2] . All these results corroborate our findings on Bactrocera dorsalis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These acetogenins are inhibitors of mitochondrial complex I and are therefore known to be neurotoxic in humans and rats. Other studies have demonstrated the effectiveness of the oil on insects of the order Diptera [17,2] . All these results corroborate our findings on Bactrocera dorsalis.…”
Section: Discussionmentioning
confidence: 96%
“…
The soursop is an oleaginous plant whose seeds are much feared for their toxicity. [1,2] . Its oil is extracted from the kernels using a soxhlet device using cyclohexane.
…”
mentioning
confidence: 99%
“…Asetogenin yang dihasilkan oleh biji A. muricata menyebabkan toksisitas pada beberapa serangga yang dikaji oleh penelti lain, misalnya larva dan imago Aedes albopictus dan Culex quinquefasciatus (Ravaomanarivo et al, 2014), kecoa dan Tenebrio melitor, Spodoptera litura (Irwan et al, 2021), menghambat aktivitas makan larva P. xylostella, menghambat pertumbuhan dan perkembangan larva dan pupa serta mematikan larva P. xylostella (Prédes Trindade et al, 2011) Pada penelitian lain ektrak A. muricata 1 g/L yang diekstraksi dengan etanol menunjukkan bahwa kemapuan ektrak tersebut mematikan iamago C. maculatus sebesar 88% pada 72 jam setelah perlakuan (Adeoye & Ewete, 2011). Diduga bahawa konsentrasi asetogenin pada A. muricata di daratan Pulau Timor lebih tinggi dibandingkan dengan daerah lain sehingga pada pada perlakuan yang sama kemampuan untuk mematikannya lebih tinggi.…”
Section: Toksisitas Ekstrak Daging Biji a Muricata Dan S Oleasa Terha...unclassified
“…Hama termasuk salah satu OPT yang dalam pengendalian dapat dilakukan secara kimia, fisik, biologis, mekanis, hayati, dan kultur teknis (Hartono, 2017). Pestisida merupakan zat yang digunakan untuk mengurangi, mencegah, atau menghancurkan hama, namun pestisida sintetik yang umum digunakan memiliki dampak yang berbahaya untuk kesehatan manusia seperti kerusakan saluran pernafasan, sistem kekebalan tubuh, bahkan dapat menimbulkan kanker (Irwan et al, 2021). Berdasarkan Undang-Undang No.…”
Section: Pendahuluanunclassified